Impact of Recent Legislation and Regulation Improvements on Business Opportunities on the Russian Insurance Market - Vayshnurs, Anton (2006)
Emerging new regulatory practices and legislative changes are among major drivers of business development and competitive advantage in heavy regulated financial services industry. Analysing recent legislative and regulatory improvements in Russian insurance industry we try to estimate potential opportunities created by these recent changes and to forecast further trends of development of Russian regulatory and legal environment. Briefly these trends could be summarised as follows: ÃÂ¢ÃÂÃÂ¢ Strengthening of the capital requirements; ÃÂ¢ÃÂÃÂ¢ Improving liquidity and profitability of insurance reserves; ÃÂ¢ÃÂÃÂ¢ Attention to corporate governance in insurance industry; ÃÂ¢ÃÂÃÂ¢ Gradual opening of the market to foreign investors and competitors; ÃÂ¢ÃÂÃÂ¢ Introduction of multiple new kinds of mandatory liability insurance and combating tax evasion insurance operations. Subject to successful implementation this measures are supposed to civilize Russian insurance market making it attractive for foreign insurance and reinsurance brokers and underwriters. Monitoring Russian insurance regulation can enable foreign insurance companies to utilise ÃÂ¢ÃÂÃÂfirst moveÃÂ¢ÃÂÃÂ opportunities as soon as they will arise in this rapidly developing market. Some of them are described below.